Efektivitas Pembelajaran Daring Di Masa Pandemi Covid 19 Bagi Mahasiswa Politeknik Bumi Akpelni Semarang - Suprihono Setyawan; Tini Utami; Devi Kusumaningrum (Sekolah Tinggi Maritim Yogyakarta, 2022)
This study aims to determine the level of effectiveness of online learning for students or cadets at the Bumi Akpelni Polytechnic semarang, with a total of 516 respondents. Research activities were carried out during the implementation of Study From Home during the Covid-19 pandemic. The application support used in this online lecture is zoom meetings, google meet and whattapp groups. This study uses a descriptive qualitative method that aims to describe the condition of natural objects with triangulation data collection techniques. From the results of the study of 516 cadets or students, it can be concluded that students or cadets choose at home as a place to learn during the pandemic, then it can also be explained that the most effective tool is a smartphone then respondents choose to use the Google Classroom application as the main alternative in online learning but it is also necessary to pay attention to the geographical conditions of each and